2020
DOI: 10.1371/journal.pone.0230144
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of the shear stress and oscillatory shear index of coronary arteries during Enhanced External Counterpulsation in patients with coronary heart disease

Abstract: BackgroundEnhanced External Counterpulsation (EECP) can chronically relieve ischemic chest pain and improve the prognosis of coronary heart disease (CHD). Despite its role in mitigating heart complications, EECP and the mechanisms behind its therapeutic nature, such as its effects on blood flow hemodynamics, are still not fully understood. This study aims to elucidate the effect of EECP on significant hemodynamic parameters in the coronary arterial tree. MethodsA finite volume method was used in conjunction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 39 publications
(59 reference statements)
1
11
0
4
Order By: Relevance
“…The mechanisms for the effects produced by EECP appear to have both a central hemodynamic component with decreased afterload, increased coronary blood flow, and a peripheral effect (passive exercise) ( Braith et al, 2012 ; Raza et al, 2017 ). In addition to the aforementioned, EECP also improves the oscillatory flow pattern in stenosed coronary arteries ( Xu et al, 2020 ). The EECP device has a large footprint (1,861,800 cm 3 ) with an approximate reported cost above $100,000 (£ 90,000) ( McKenna et al, 2010 ).…”
Section: Enhanced External Counterpulsationmentioning
confidence: 99%
“…The mechanisms for the effects produced by EECP appear to have both a central hemodynamic component with decreased afterload, increased coronary blood flow, and a peripheral effect (passive exercise) ( Braith et al, 2012 ; Raza et al, 2017 ). In addition to the aforementioned, EECP also improves the oscillatory flow pattern in stenosed coronary arteries ( Xu et al, 2020 ). The EECP device has a large footprint (1,861,800 cm 3 ) with an approximate reported cost above $100,000 (£ 90,000) ( McKenna et al, 2010 ).…”
Section: Enhanced External Counterpulsationmentioning
confidence: 99%
“…However, the influence of EECP on WSS-derived hemodynamic factors remains unclear. Xu et al ( 2020 ) reported that EECP treatment reduced the surface area ratio of the time-averaged wall shear stress risk area (SAR–TAWSS) and the oscillatory shear index risk area (SAR–OSI) in coronary arteries of patients who had undergone stent implantation or coronary artery bypass grafting.…”
Section: Introductionmentioning
confidence: 99%
“…Xu L. и соавт. [19] при помощи геометрических моделей на основе КТ-ангиографии и сфигмограммы пульсовой волны продемонстрировали улучшение гемодинамических условий в аорте и коронарном русле при проведении УНКП. При исходно более выраженном стенозе (≥75% площади) авторами отмечено статистически значимое улучшение среднего по времени напряжения сдвига стенки (с 12,3% до 6,7%) и индекса колебательного сдвига (с 6,8% до 2,5%) [19].…”
Section: материал и методыunclassified
“…В большинстве исследований, посвященных УНКП у пациентов с ИБС, в т. ч., осложненной ХСН, изучение эффектов (0-12 мес по окончании лечения) проводилось после стандартного однократного курса (35 ч в год) [14][15][16][17][19][20][21][22][23][24]. При этом не подразумевалось регулярное использование УНКП в лечении больных ИБС, в том числе, осложненной ХСН.…”
Section: материал и методыunclassified